Comparison of Defined Course Doses (DCDvet) for Blanket and Selective Antimicrobial Dry Cow Therapy on Conventional and Organic Farms - Clair L. Firth; Annemarie Käsbohrer; Christa Egger-Danner; Klemens Fuchs; Beate Pinior; Franz-Ferdinand Roch; Walter Obritzhauser (Animals, 2019)
Antimicrobial use in livestock production is a controversial subject. While antimicrobials should be used as little as possible, it is still necessary, from both an animal health and welfare point of view, to treat infected animals. The study presented here aimed to analyse antimicrobial use on Austrian dairy farms by calculating the number of Defined Course Doses (DCDvet) administered per cow and year for dry cow therapy. Antimicrobial use was analysed by production system and whether farmers stated that they used blanket dry cow therapy (i.e., all cows in the herd were treated) or selective dry cow therapy (i.e., only cows with a positive bacteriological culture or current/recent history of udder disease were treated). A statistically significant difference (p < 0.001) was determined between antimicrobial use for blanket (median DCDvet/cow/year: 0.88) and selective dry cow therapy (median DCDvet/cow/year: 0.41). The difference between antimicrobial use on conventional and organic farms for dry cow therapy as a whole, however, was not statistically significant (p = 0.22) (median DCDvet/cow/year: 0.68 for conventional; 0.53 for organic farms). This analysis demonstrates that selective dry cow therapy leads to a lower overall use of antimicrobials and can assist in a more prudent use of antimicrobials on dairy farms.